Striking a Balance : Toward a Comprehensive Housing Policy for a Post-COVID Colombia - World Bank (World Bank, Washington, DC, 2021)
Government initiatives to reduce the housing deficit in Colombia go back more than a hundred years, but it was only after the creation of the Ministry of Housing as an independent agency, a decade ago, that national housing policy took on the relevance that it has today. Since then, Colombia has made substantial progress. Building on the progress made by previous governments, since 2018 the national government has promoted a comprehensive, inclusive, and sustainable housing policy, which has led to notable improvements, and enabled significant progress towards achieving the sustainable development goals (SDGs) and implementing best practices in the region. The past two and a half years have been full of positive results and unimaginable challenges, including the Coronavirus disease 2019 (COVID-19) pandemic. In this context, national housing policy in Colombia has started to undergo a transition towards a truly integrated approach, one which addresses several of the challenges discussed in the report. One of the key aspects of this transition is the main thesis developed in this report: the need to intensify housing policy’s focus on the qualitative housing deficit after years of concentrated efforts to reduce the quantitative deficit.